2014
DOI: 10.5194/se-5-1223-2014
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conditions during deformation of partially molten crust from TitaniQ geothermometry: rheological implications for the anatectic domain of the Araçuaí belt, eastern Brazil

Abstract: Abstract. During the Neoproterozoic orogeny, the middle crust of the Araçuaí belt underwent widespread partial melting. At the regional scale, this anatectic domain is characterized by a progressive rotation of the flow direction from south to north, suggesting a 3-D deformation of the anatectic middle crust. To better determine whether melt volumes present in the anatectic middle crust of the Araçuaí orogen were large enough to allow a combination of gravity-driven and convergence-driven deformation, we used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 47 publications
2
44
0
3
Order By: Relevance
“…Temperature estimates using the TitaniQ (Titanium-in-quartz) geothermometer presented by Cavalcante et al (2014) suggest that the minimum temperature at which quartz grains crystallized, and therefore the minimum temperatures needed to trigger partial melting, was ~750 °C. Cavalcante et al (2014), using traditional exchange geothermobarometers in kinzigitic migmatites neighboring the Carlos Chagas unit, suggested that peak metamorphism occurred at 750 to 840 ± 50 °C at pressures ranging from 650 to 700 ± 100 MPa.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Temperature estimates using the TitaniQ (Titanium-in-quartz) geothermometer presented by Cavalcante et al (2014) suggest that the minimum temperature at which quartz grains crystallized, and therefore the minimum temperatures needed to trigger partial melting, was ~750 °C. Cavalcante et al (2014), using traditional exchange geothermobarometers in kinzigitic migmatites neighboring the Carlos Chagas unit, suggested that peak metamorphism occurred at 750 to 840 ± 50 °C at pressures ranging from 650 to 700 ± 100 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…2a), or interconnected networks of melt, in which thick leucosomes (3-30 cm) are highly discordant to the foliation (Fig. 2c); these leucosome networks, together with the aforementioned migmatitic structures, suggest a minimum of 30% melt content in the migmatitic system (e.g., Cavalcante et al 2014;Sawyer 2008). In many outcrops of diatexites, the leucosomes may occupy up to 70% of the migmatite, suggesting amounts of melt considerably higher than 30%.…”
Section: Field Characteristics Of the Carlos Chagas Anatexitementioning
confidence: 97%
See 3 more Smart Citations